2021
DOI: 10.1111/rsp3.12404
|View full text |Cite
|
Sign up to set email alerts
|

Regional competitiveness of a post‐mining city in tourism: Ombilin coal mining heritage of Sawahlunto, Indonesia

Abstract: This paper explores the role of mining heritage tourism attributes on a destination's overall performance, and examines its competitiveness with other cities within the same regional boundary. Relevance-determinance analysis (RDA) and competitive-performance analysis (CPA) were

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 56 publications
0
1
0
Order By: Relevance
“…Such areas should be outstanding and facilitate the development, improvement or changes pertaining to wellness tourism, including the local area's appeal, which could promote the destination to attract wellness tourists. This was consistent with studies by Akin et al (2021), Armis and Kanegae (2021), Bogale and Wondirad (2019), Ferreira and Perks (2020), Mustafa et al (2021) and Woyo and Slabbert (2021), who found an area with abundant natural resources, exquisite sceneries, human-made natural tourist attractions in harmony with the nature, outstanding architecture with unique local identity and variety of culture and tradition (Dos Anjos and Da Rosa, 2021;Goffi and Cucculelli, 2019;Hernández-Rojas et al, 2021;Wardana et al, 2019). Gajić et al (2018) and Petrović et al (2018) emphasised the preparation of adequate medical or wellness service facilities for tourists' needs, such as state-to-the-art equipment.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Such areas should be outstanding and facilitate the development, improvement or changes pertaining to wellness tourism, including the local area's appeal, which could promote the destination to attract wellness tourists. This was consistent with studies by Akin et al (2021), Armis and Kanegae (2021), Bogale and Wondirad (2019), Ferreira and Perks (2020), Mustafa et al (2021) and Woyo and Slabbert (2021), who found an area with abundant natural resources, exquisite sceneries, human-made natural tourist attractions in harmony with the nature, outstanding architecture with unique local identity and variety of culture and tradition (Dos Anjos and Da Rosa, 2021;Goffi and Cucculelli, 2019;Hernández-Rojas et al, 2021;Wardana et al, 2019). Gajić et al (2018) and Petrović et al (2018) emphasised the preparation of adequate medical or wellness service facilities for tourists' needs, such as state-to-the-art equipment.…”
Section: Discussionsupporting
confidence: 85%
“…This finding was consistent with Akin et al (2021), who found that the destination's overall image, the expertise of staff in tourism and services and business expertise in providing wellness tourism services were important factors in promoting the destination, thereby improving competitiveness. Altinay and Kozak (2021), Armis and Kanegae (2021), Ferreira and Perks (2020) and Woyo and Slabbert (2021) emphasised the importance of tourists' personal safety and hygienic healthcare services at the destination. Furthermore, Bogale and Wondirad (2019), Gajić et al (2018), Mustafa et al (2021), andNeto et al (2020) found that an area or destination with educational institutions providing knowledge about wellness tourism administration and management, hospitals and businesses providing healthcare services, friendliness of the local people (Petrović et al, 2018;Woyo and Slabbert, 2021) and local telecommunications were important factors in attracting wellness tourists, which could improve the destination's competitiveness.…”
Section: Discussionmentioning
confidence: 99%
“…Post-mining tourism development in Sawahlunto is oriented toward creating a heritage-based tourist town (Armis & Kanegae, 2021). Concurrently, the city's creative industry development prioritizes performing arts, fashion, culinary, and crafts (Wahyuni & Khaidir, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies elucidated the transfor-mation of Sawahlunto from a mining town into a tourist destination, as conducted by Armis and Kanegae (2020), Cheris, Repi, and Amalia, (2020), Armis and Kanegae (2021) and Syafrini et al (2021). However, there is limited discussion on the city's transformation into the realm of the creative industry and the social impact it has generated, such as the shift in the community's professions from coal miners to crafts workers producing souvenirs and jewelry from coal.…”
Section: Introductionmentioning
confidence: 99%
“…Our research brings a new perspective to the previous literature in relation to loyalty and citizen satisfaction in urban areas, since the expected quality is separated in territorial planning, municipal services and citizen’s environmental experience [ 36 , 37 ]. Once the citizens have decided to establish their residence in the urban area, the perceived quality is studied in the same dimensions.…”
Section: Introductionmentioning
confidence: 99%